Jugaad innovation : think frugal, be flexible, generate breakthrough growth - Radjou, Navi.; Prabhu, Jaideep C.; Ahuja, Simone (San Francisco, CA : Jossey-Bass, 2012)
'A frugal and flexible approach to innovation for the 21st centuryInnovation is a key directive at companies worldwide. But in these tough times, we can't rely on the old formula that has sustained innovation efforts for decades--expensive R&D projects and highly-structured innovation processes. Jugaad Innovation argues the West must look to places like India, Brazil, and China for a new approach to frugal and flexible innovation. The authors show how in these emerging markets, jugaad (a Hindi word meaning an improvised solution born from ingenuity and cleverness) is leading to dramatic growth and how Western companies can adopt jugaad innovation to succeed in our hypercompetitive world. Outlines the seven principles of jugaad innovation: Seek opportunity in adversity, do more with less, think and act flexibly, keep it simple, include the margin, and follow your heart Features twenty case studies on large corporations from around the world--Google, Facebook, 3M, Apple, Best Buy, GE, IBM, Nokia, Procter & Gamble, PepsiCo, Tata Group, and more--that are actively practicing jugaad innovation The authors blog regularly at Harvard Business Review; their work has been profiled in BusinessWeek, MIT Sloan Management Review, The Financial Times, The Economist, and more Filled with previously untold and engaging stories of resourceful jugaad innovators and entrepreneurs in emerging markets and the United States This groundbreaking book shows leaders everywhere why the time is right for jugaad to emerge as a powerful business tool in the West--and how to bring jugaad practices to their organizations.'--
Includes bibliographical references and index.
Keywords: Technological innovations -- Case studies; Adaptability (Psychology) -- Case studies